2020
DOI: 10.5999/aps.2019.00598
|View full text |Cite
|
Sign up to set email alerts
|

One-stage nipple and breast reconstruction using a deep inferior epigastric perforator flap after a skin-sparing mastectomy

Abstract: Background Nipple reconstruction is usually performed as a delayed procedure in patients with breast cancer who undergo skin-sparing mastectomy and breast reconstruction surgery using a deep inferior epigastric perforator (DIEP) flap. The authors designed this study to evaluate the utility of breast reconstruction based on a DIEP flap and immediate nipple reconstruction. Methods A retrospective review was conducted of all patients who underwent breast reconstruction performed by a single plastic surgeon from O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Immediate reconstruction of the nipple in patients having mastectomy and reconstruction has also been previously reported. 11 , 12 There are also other TM techniques described to improve the cosmetic outcome following excision of central tumors without the reconstruction of the NAC. 3 , 13 Johnson et al 3 describe a technical modification of the Grisotti flap in patients with short nipple to inferior mammary crease distance.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate reconstruction of the nipple in patients having mastectomy and reconstruction has also been previously reported. 11 , 12 There are also other TM techniques described to improve the cosmetic outcome following excision of central tumors without the reconstruction of the NAC. 3 , 13 Johnson et al 3 describe a technical modification of the Grisotti flap in patients with short nipple to inferior mammary crease distance.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have reported series of single-stage autologous breast reconstructions (Cho et al, 2020;Haykal & Guay, 2009;Laporta et al, 2016;Levine et al, 2013;Losken et al, 2002;Wade et al, 2016) after SSM or nipple sparing mastectomy (NSM). Losken 2016) reported a one-stage DIEP flap reconstruction presenting a contralateral symmetrization algorithm that led to aesthetic outcomes and patient satisfaction comparable to staged procedures.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have reported series of single‐stage autologous breast reconstructions (Cho et al, 2020; Haykal & Guay, 2009; Laporta et al, 2016; Levine et al, 2013; Losken et al, 2002; Wade et al, 2016) after SSM or nipple sparing mastectomy (NSM). Losken et al (2002) presented a series of 1394 patients, without comparing outcomes between simultaneous and staged procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations